On the Kernel of Black-Scholes Equation related to the risk neutrality for cash-or-nothing options - Amnuay Kananthai (2018)
© 2017 by the Mathematical Association of Thailand. All rights reserved. In this paper, we studied the Kernel or the elementary solution of the Black-Scholes Equation and we can relate such Kernel to the risk neutrality for cash-or-nothing option. We obtained interesting new results.